The International System's Structure and Identification of Salafi- Extremist Islam - علی آدمی; عبداله مرادی (Faṣlnāmah-i Pizhūhish/hā-yi Rāhburdī-i Siyāsat, 2018)
Salafi thoughts and the phenomenon of violent extremism are frequent subjects in political and international studies. A comprehensive study in the field of international relations that based on the interaction between structure and agency, can explain the issue. The main objective of this paper is to study the Salafi- Extremist Islam. Salafist- Extremist groups tend to perform violent struggle to gain power and overthrow governments in order to restore the Islamic caliphate. The main question of this article is that: how International System has affected Salafi- Extremist Islam, during the post-cold war era? Theoretical framework of this paper is Constructivism. Research method in qualitative content analysis. In this regard, we tried to analyze this extremist movement and show how the international system affected these groups.